Adjustment of Peruvian family violence to the psychobiogeographic theory of mental health - León, Federico (2012)
The psychobiogeographic theory, considering the extent of exposure to ultraviolet radiation, predicts a latitudinal variation of mental health. An analysis of questionnaire responses from 12,604 women in the Peru 2000 Demographic and Family Health Survey was undertaken to test the hypothesis that physical and psychological violence exerted by husbands and parents against women increases with distance from the Equator. The observed effects of latitude were consistent with the theory in the Pacific desert, Sierra steppe, Puna, and Yunga sites, but not in the Amazon eco-region, which could be due to an excess of vitamin D produced north of 5º 50’ S. The theory’s hypotheses concerning urbanization and the Humboldt Current were supported, but the one on altitude was not